The Immunoenhancing properties of living Rhizobium meliloti in experimental animals - Al-Joofy K. Ikbal (College of Pharmacy / Mustansiriyah University, 2006)
This study was designed to shed some light on the influence of living Rhizobium meliloti (non pathogenic bacteria) on the immune system of mature mice. Thirty male mice, 6-8 weeks old, 19-22gm weight divided into two groups, test group (n.=20), orally administrated with 100μl (4x106 CFU/ml normal saline) for 12successive days, at the same time and rout control group (n.=10) received 100 μl of sterile normal saline. Tests for immunomodulation effects of this bacteria were applied after immunization of both groups with 0.2ml, (10% sheep red blood cells) interaperitonialy on day 4 and 8 of scheduale. Arthus reaction, delayed type hypersensitivity, E-rosette forming test, serum antibody level, phagocytosis index and nitro blue tetrazolium reduction were assessed on day 11 and 12 of program, mean while effect of the bacteria on the body weight of each group were studied. Interestingly, this non-pathogenic living bacteria showed immunopotentiating activities in experimental animals reflected by these in vivo & in vitro assays.